The Archaeal Elongation Factor EF-2 Induces the Release of aIF6 From 50S Ribosomal Subunit - Lo Gullo, Giada; De Santis, Maria Luisa; Paiardini, Alessandro; Rosignoli, Serena; Romagnoli, Alice; La Teana, Anna; Londei, Paola; Benelli, Dario (Frontiers in Microbiology, 2021)
The translation factor IF6 is a protein of about 25 kDa shared by the Archaea and the Eukarya but absent in Bacteria. It acts as a ribosome anti-association factor that binds to the large subunit preventing the joining to the small subunit. It must be released from the large ribosomal subunit to permit its entry to the translation cycle. In Eukarya, this process occurs by the coordinated action of the GTPase Efl1 and the docking protein SBDS. Archaea do not possess a homologue of the former factor while they have a homologue of SBDS. In the past, we have determined the function and ribosomal localization of the archaeal (Sulfolobus solfataricus) IF6 homologue (aIF6) highlighting its similarity to the eukaryotic counterpart. Here we analyzed the mechanism of aIF6 release from the large ribosomal subunit. We found that, similarly to the Eukarya, detachment of aIF6 from the 50S subunit requires a GTPase activity which involves the archaeal elongation factor 2 (aEF-2). However, the release of aIF6 from the 50S subunits does not require the archaeal homologue of SBDS, being on the contrary inhibited by its presence. Molecular modeling, using published structural data of closely related homologous proteins, elucidated the mechanistic interplay between the aIF6, aSBDS and aEF2 on the ribosome surface. The results suggest that a conformational rearrangement of aEF2, upon GTP hydrolysis, promotes aIF6 ejection. On the other hand, aSBDS and aEF2 share the same binding site, whose occupation by SBDS prevents aEF2 binding, thereby inhibiting aIF6 release.